Characteristics of abdominal herniation and its associations among patients operated in a Sudanese tertiary hospital: a retrospective review - Ahmed Abdellateef Hassan Bakry; Khabab Abbasher Hussien Mohamed Ahmed; Mohammed Mahmoud Fadelallah Eljack; Ghassan E. Mustafa Ahmed (BMC Surgery)
Abstract Background & aims Hernia is a very common surgical condition affecting all ages and both sexes. Data regarding abdominal wall hernias is essential to hernia management in an institution. With the absence of data regarding the prevalence, characteristics, and associations of abdominal wall hernias in Sudanese patients, we aimed to describe and find the possible differences in the spectrum of abdominal hernias, their rates, and associated predisposing factors. Methodology This was a retrospective cross-sectional chart review of surgical patients admitted at a Sudanese tertiary teaching Hospital, Department of Surgery, from January 2019-December 2021. Data were collected from the medical records using a checklist. The data obtained included age, gender, occupation, chronic medical conditions, past medical history (PMH), and year of admission. Data were analyzed using SPSS 22. Results Results showed that between January 2019 and December 2021, a total of 1158 patients were admitted to the department of surgery, and abdominal hernia had a frequency of 16.23% (n = 188). There was a male predominance (55.3%), ages below 20 years constituted the majority of cases (45.2%), and those between (50–60 years) were the least. The most frequent subtype was the inguinal hernia. The association between sociodemographic variables, PMH, chronic medical conditions, and the diagnosis was found to be statistically significant. The rate of recurrence was found to be 10.1%. Conclusion There was a high rate of abdominal Herniation, and a difference between subtypes of abdominal herniation regarding demographic data, past medical history, and comorbidities.